Determinan Penghindaran Pajak di Masa Pandemi Covid-19: Studi Empiris Perusahaan Jasa Keuangan dan Asuransi - Isti Anah; Amir Hidayatulloh (Universitas Negeri Padang, 2022)
This study aims to analyze the factors that influence tax avoidance during the COVID-19 pandemic, especially in financial services and insurance companies. The population of this study are companies listed on the Indonesia Stock Exchange. The research sample is the financial services and insurance sector companies listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling. The data used in this study amounted to 61 data. The data analysis of this research used multiple linear regression analysis. This study obtained the results that tax avoidance in financial services and insurance companies is influenced by profitability. However, it is not affected by leverage, firm size, and institutional ownership.Keywords: Tax Avoidance, Profitability, Leverage, Firm Size, Institutional Ownership